Digital Agriculture Profile: Côte d'Ivoire - Traoré, Sékou Amadou; Mabaya, Edward; Afun-Ogidan, Olukemi Dolly; Ajilore, Bunmi; Girvetz, Evan Hartunian; Jarvis, Andy; Kropff, Wietske (Food and Agriculture Organization of the United Nations, 2021)
This Digital Agriculture Profile for Côte D’Ivoire leverages the expertise of stakeholders to evaluate the current landscape of digital agriculture in Côte D’Ivoire, including its key players across value chains, the main barriers they face, and the potential to overcome these barriers through the adoption of innovative technologies.